KOMPONEN-KOMPONEN KURIKULUM DALAM SISTEM PEMBELAJARAN - Henni Sukmawati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2021)
In general, the curriculum is a design that makes a set of subjects or material to be studied, or that teachers teach to students. The curriculum and teaching are an integral part because the curriculum provides learning directions and curriculum refers to program planning and learning experiences while learning refers to teaching methodologies and activities. Therefore, the curriculum as a system that has components that support each other and are interrelated with one another, namely the objective component which is the direction of education, the component of the learning experience, the component of the strategy for achieving the goals and the evaluation component. The components that make the curriculum system up and result to teaching and teaching systems are what guide teachers and manage the teaching and learning process in the classroom.